Foucault e as utopias das luzes: panóptico e esclarecimento - Batista, Fábio (2019)
This dissertation deals with the thought of Foucault from a perspective that seeks to understand his conception of enlightenment from a moral, ethical and political perspective. The dissertation proposes that one can find in Foucault a double conception of enlightenment, the analysis of Bentham's panopticon and the study of Kant's essay on enlightenment. It argues that it is a Foucauldian genealogy of two Utopias of Lights, the technical-disciplinary panopticon and the ethical-political enlightenment, from which comes an image of modernity that, paradoxically, tends to discipline and emancipation at the same time: the docile body and reflected indocility. For that, texts of Foucault are used, especially of the decades of 1970 and 1980, as well as texts of philosophers of different periods of the history of philosophy. This dissertation is divided into three chapters. The first explores the notion of utopia in three moments: first, with Thomas More, creator of the notion of utopia; second of refusing the notion of utopia; and, third, an understanding of utopia in which it has a positive value. Having established this, this dissertation passes to Foucault's notion of utopia, which imposes a certain inflection on the three earlier conceptions when articulating body and utopia, in order to show that the body is the matrix of utopia; and, still in chapter one, there is reference to the Foucauldian notion of heterotopia. The second chapter deals with the panopticon-utopia and its heterotopias, showing how Foucault makes the genealogy of this utopia: he begins with the origin of problems related to surveillance, architecture and socio-political control; he passes to the emergence of the panopticon-utopia in Bentham's thought: architecture and transferable functioning of this utopia of inspection; then he indicates which are the panopticon heterotopias, especially the prison and the psychiatric asylum, showing how these modern institutions are articulated with Bentham's panopticon program. Finally, the third chapter shows the problems that led to Kant's subsequent formulation of the enlightenment-utopia, especially his contemporaries' refusal to accept the religious sanction of marriage. Then it goes on to consider the enlightenment-utopia from Kant's perspective. It shows the emergence of this utopia; the attitude of modernity outlined by the enlightenment-utopia and the way in which Foucault stands before it as well as its implications for his understanding of the question of what philosophy is. This chapter closes with a section dealing with the struggles against the techniques of power-knowledge of a disciplinary and pastoral type, understood as anarchic struggles in displacement relative to the Kantian enlightenment; it also interprets that one can speak of at least one enlightenment-type heterotopia, which is closely linked to Foucault, the Vincennes Experimental University Center.